Articulations of antimicrobial resistance in trade union financed journals for nurses in Scandinavia – A Foucauldian perspective. Issue 3 (23rd January 2021) - Glasdam, Stinne; Loodin, Henrik; Wrigstad, Jonas
Abstract: Antimicrobial resistance (AMR) in bacterial infections is a growing threat to humanity and a challenge to healthcare systems worldwide. Healthcare professionals have an important role in preventing AMR and the spreading of infections. This article focuses on trade union financed journals for nurses in Scandinavia studying how the journals articulate AMR to its readership. A systematic literature search over an eleven‐year period was conducted, using web‐based national trade union financed journals, searching for 'bacteria' and 'resistance'. A thematic analysis, inspired by Foucault's concepts of power and governmentality, was made of 131 texts to understand, which kind of practices, strategies and policies the journals frame regarding AMR. The time period studied resulted in the recognition of four separate themes: the horror scenario, the 'dangerous' other, healthcare professionals as a source of resistance development and AMR as a field of research and producer of research qualifications. The study concludes that the journals tend: to present AMR in apocalyptic terms with more research and pharmaceutical industries needed for avoidance; to point out problems in other countries, populations, and sometimes nurses' working conditions, but primarily with other professionals' behaviour; and lastly, to present the nurse as a good fairy and disciplinator of doctors.